The SH3 Domain Directs Acto-Myosin-Dependent Targeting of v-Src to Focal Adhesions via Phosphatidylinositol 3-Kinase - Fincham, Valerie J. (American Society for Microbiology, 2000)
The v-Src oncoprotein is translocated to integrin-linked focal adhesions, where its tyrosine kinase activity induces adhesion disruption and cell transformation. We previously demonstrated that the intracellular targeting of Src is dependent on the actin cytoskeleton, under the control of the Rho family of small G proteins. However, the assembly of v-Src into focal adhesions does not require its catalytic activity or myristylation-dependent membrane association. Here, we report that the SH3 domain is essential for the assembly of focal adhesions containing the oncoprotein by mediating a switch from a microtubule-dependent, perinuclear localization to actin-associated focal adhesions; furthermore, v-Src translocation to focal adhesions requires myosin activity, at least under normal conditions when the actin cytoskeleton is being dynamically regulated. Although the SH3 domain of v-Src is also necessary for its association with focal adhesion kinase (FAK), which is often considered a likely candidate mediator of focal adhesion targeting via its carboxy-terminal targeting sequence, we show here that binding to FAK is not essential for the targeting of v-Src to focal adhesions. The p85 regulatory subunit of phosphatidylinositol (PI) 3-kinase also associates with v-Src in an SH3-dependent manner, but in this case inhibition of PI 3-kinase activity suppressed assembly of focal adhesions containing the oncoprotein. Thus, the Src SH3 domain, which binds PI 3-kinase and which is necessary for activation of Akt downstream, is required for the actin-dependent targeting of v-Src to focal adhesions.